DESIGN AND CONSTRUCTION OF BIPEDAL HUMANOID ROBOT WITH FUZZY ALGORITHM AND INVERSE KINEMATICS IMPLEMENTATION FOR STATIC BALANCE CONTROL - SUTANTO (NIM : 132 05 038); Pembimbing : Dr. Kusprasapta Mutijarsa, S.T., M.T.; Dr. Ir. H, GIOVANNI
Bipedal humanoid robot is a robot that have mechanical structure like human body and using its legs for locomotion. To be able to do its tasks, firstly the bipedal humanoid robot must have a good locomotion ability, that is the ability to walk in balance. The ability to walk in balance includes the concept of dynamic balance, which is pretty complicated to be implemented. Therefore, before working on dynamic balance, it is good to start with static balance. In this final project research, design and construction of bipedal humanoid robot that implements static balance control system is done, which consists of mechanical system (or platform), hardware, and software. The problem of static balance control which is considered is the condition when the bipedal humanoid robot is standing on a balance board with certain tilt angle. The mechanical system design is aimed at getting a design that make the robot able to walk in balance. The sensor is using a 3-axis accelerometer. The data processing system is using an AVR microcontroller system with ATmega128. The actuator is using servo motors. The software of the static balance control system is implementing Sugeno-style fuzzy inference system and inverse kinematics. The design and construction of the bipedal humanoid robot that implements static balance control system has successfully been done. Testing shows that the bipedal humanoid robot has been able to sustain static balance while standing on a balance board with tilt angle up to 20Ã‚Â°, due to mechanical system limitation. The next stage of research is aimed at dynamic balance control system.